Developing An Informed, Educated And Empowered Citizenry - Arua, Godwin Nwachukwu; Eze, Celestine onyebuchi; Ezeanuna, Ginika `; Ukwuaba, Helen Obioma (Qualitative and Quantitative Methods in Libraries, 2019)
Abstract Information is at the core of education and that it has a democratic, liberatory power that will give all members of the society the equality of access to the society’s power. We find ourselves in a rapidly growing and complex digital environment which has in turn increased our dependence on information. Modern society can develop if people acquire competencies of a reasonable and responsible handling of new technologies. The libraries, librarians, and educators have important role to play in this context. Providing the right information to the right persons at the right time is the key to the success of any in institution. Information literacy lies at the core of lifelong learning. Information literacy enables people to interpret and make informed judgments and decisions as users of information sources and to become producers of information in their own right too. Transforming all levels of education and moving beyond the boundaries of information literacy as a library only issue, librarians, educators, and administrators must continue to develop tools of collaboration and communication about information literacy in the context of teaching, learning and research. This is the thrust of this paper.